Penerapan Website SIASN dalam Pelayanan Internal Manajemen ASN - Endang Widya Ningsih; Zulfina Adriani; Dwi Kurniawan (Jurnal Ilmiah Ekonomi, Akuntansi, dan Pajak, 2025)
This study aims to analyze the implementation of the State Civil Apparatus Information System (SIASN) website in internal ASN management services at the Jambi Animal, Fish and Plant Quarantine Center. This study uses a qualitative research method with a case study approach to analyze the impact of the implementation of the SIASN website on service speed, time efficiency, or obstacles and challenges faced. The results of this study indicate that the implementation of SIASN has succeeded in reducing the time in various ASN administration processes, which previously took several days to only a matter of hours. In addition, this system also increases transparency in employee data management. The main supporting factors for the success of SIASN are the availability of adequate infrastructure and HR competence in operating the system. Overall, this study confirms that SIASN has a significant effect on increasing the efficiency and effectiveness of internal ASN management services.